Remarkable response to anti-PD1 immunotherapy in refractory metastatic high-grade myxofibrosarcoma patient: A case report. Issue 12 (26th March 2021) - Luo, Yi; Min, Li; Zhou, Yong; Tang, Fan; Lu, Minxun; Xie, Hongmei; Wang, Yitian; Duan, Hong; Zhang, Wenli; Tu, Chongqi
Abstract: Introduction: Myxofibrosarcoma (MFS) is a locally aggressive tumor and has the potential to be fatal because of distant metastasis. Immunotherapy targeting either programmed cell death protein 1 (PD-1) or programmed death ligand 1 (PD-L1) has recently shown a curative effect on multiple cancers including melanoma, non-small cell lung cancer, and renal cell carcinoma. Although the immunotherapy has been applied in sarcoma, there is little information about the efficiency to treat metastatic MFS. Patient concerns: A 42-year-old male presented to the clinic with a mass in the left thigh. Mass resection and ligament replacement surgery were performed. Diagnoses: The patient was diagnosed as high-grade MFS (federation nationale des centres de lutte contre le cancer, Grade 3) with pulmonary metastasis. Interventions: In the past few years, he was treated with surgery, chemoradiotherapy, and Anlotinib (an angiogenesis inhibitor), but the metastatic lesion continued to progress. About 40% to 50% of tumor cells in his pulmonary tissues were showed positive PD-L1 expression and his tumor mutational burden was 215Muts. Thus, he received Camrelizumab (PD-1 inhibitor). Outcomes: Six months after the initiating immunotherapy of Camrelizumab, the size of pulmonary lesions showed marked shrinkage, indicating a partial response. After a follow-up of 18 months, the patient remained in good condition without progressive disease. Conclusion: This case described here demonstrated that immunotherapy of PD-1 inhibitor is a promising treatment option for refractory MFS with PD-L1 positive or tumor mutational burden -high, which could contribute to effective tumor response.